Tetraalkoxyphenanthrene‐Fused Dehydroannulenes: Synthesis, Self‐Assembly, and Electronic, Optical, and Electrochemical Properties. Issue 36 (22nd July 2013) - Kato, Shin‐ichiro; Takahashi, Nobutaka; Tanaka, Hidekazu; Kobayashi, Atsushi; Yoshihara, Toshitada; Tobita, Seiji; Yamanobe, Takeshi; Uehara, Hiroki; Nakamura, Yosuke
Abstract Novel tetraalkoxyphenanthrene‐fused dehydro[12]‐, [18]‐, and [24]annulenes 1–3 were synthesized by using Cu‐mediated or Pd‐catalyzed oxidative macrocyclization reactions as key steps, and their electronic, optical, and electrochemical properties have been investigated in detail. X‐ray crystallographic analysis of a single crystal of 1 a demonstrated that the molecules were arranged longitudinally in a slipped π‐stacked fashion to form a 1D column. 1H NMR and UV/Vis spectroscopic and cyclic voltammetric analysis in conjugation with nucleus‐independent chemical shift (NICS) calculations for 1–3 support that the annulation at the 9, 10‐positions of phenanthrene to the dehydroannulene ring enhances the tropicity and decreases the HOMO–LUMO gaps of the molecules relative to the benzannulation and that 1 possesses an antiaromatic character. Self‐association behavior due to π–π stacking in CDCl3 was observed for 1 and 2 and was quantified by concentration‐dependent 1H NMR spectroscopic measurements. The self‐assembly of 1 and 2 into well‐defined 1D superstructures with high aspect ratios were obtained, and the morphology and crystallinity of these compounds were investigated by means of SEM and wide‐angle X‐ray diffraction (WAXD) measurements. Furthermore, it was shown that 1 b and 2 b display liquid‐crystalline phases by means of differential scanning calorimetry, polarizing optical microscopy, and variable‐temperature WAXD measurements.